Assessing Patient Satisfaction in an Internal Medicine Polyclinic Using Cartesian Analysis: A Case Study at Luwuk Regional Hospital - Lanyumba, Fitrianty Sutadi; Pongsampe, Gebby; Herawati, Herawati; Kanan, Maria; Sattu, Marselina; Bidullah, Ramli; Dwi Gunawan, Nur Hendra (Journal of Health and Nutrition Research, 2025)
Good service quality is one of the important factors in trying to create consumer satisfaction. Indicators on the SERVQUAL instrument can be used to measure the level of satisfaction with the quality of health services. This study aims to analyse the satisfaction of internal medicine patients at the polyclinic at the Luwuk Regional General Hospital using a Cartesian diagram. This type of research is an observational analysis where the sample size is 125 internal medicine polyclinic patients, with sampling techniques, namely accidental sampling. The data obtained was processed using SPSS and analysed using a Cartesian diagram. The results of the study showed that the total performance value (xi) was 77.664, the total expectation value (yi) was 85.668, and the total value of the level of suitability (TKI) was 90.65, where the criteria of the assessment were the criteria of being very satisfied. The Cartesian analysis categorized the service attributes in the hospital's internal medicine polyclinic into four quadrants, identifying high-priority areas for improvement, namely problems with registration procedures, service schedules, and attention to patient complaints, while the attributes whose performance needed to be maintained were related to staff responsiveness. Hospital management needs to maintain good attribute values so that it can provide services that are fast, precise, open, simple, easy to implement, and non-discriminatory